2014
DOI: 10.1590/s1519-99402014000200010
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho e perfil sérico bioquímico de frangos de corte alimentados com rações contendo produtos homeopáticos

Abstract: O estudo foi realizado com o objetivo de avaliar o efeito da inclusão de produtos homeopáticos sobre o desempenho e perfil bioquímico sérico de frangos de corte. O delineamento experimental utilizado foi inteiramente casualizado com quatro tratamentos e oito repetições de 20 aves cada, totalizando 640 pintos de corte, machos. Os tratamentos avaliados foram: Controle (dieta sem inclusão de produtos homeopáticos), Fator Pró aves® (FP) (fornecido do 1º aos 42o dias de idade), Fator Estresse aves® (FE) (fornecido … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
4
0
3
Order By: Relevance
“…Contrary to this study, Santos et al (2014) evaluated the effects of the inclusion of different homoeopathic products on the performance and serum biochemical profile of quails and reported that the homoeopathic product Factor Pro bird® supplied from the 1st to the 42nd days resulted in decreased cholesterol levels. In short, the serum biochemical profile of quails was considered healthy and without the interference of homoeopathic doses, thus being included in the diet without prejudice to animal health.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Contrary to this study, Santos et al (2014) evaluated the effects of the inclusion of different homoeopathic products on the performance and serum biochemical profile of quails and reported that the homoeopathic product Factor Pro bird® supplied from the 1st to the 42nd days resulted in decreased cholesterol levels. In short, the serum biochemical profile of quails was considered healthy and without the interference of homoeopathic doses, thus being included in the diet without prejudice to animal health.…”
Section: Resultsmentioning
confidence: 84%
“…The homoeopathic practice is an alternative to allopathic medications. It has a lower cost and its administration is easy because it can be diluted in water or mixed with feed or premix (Santos et al, 2014). There is a decrease in restraints and possible trauma due to excessive management of animals (L. C. C. Costa et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…De acordo com Santos et al (2014), o colesterol é um dos constituintes da estrutura das membranas celulares, participa da síntese de ácidos biliares e hormônios esteroides. Entretanto, níveis elevados de colesterol séricos podem ser relacionados a possíveis problemas cardíacos, portanto, a redução desta substância no organismo torna-se desejada, o que pode ser constatado neste estudo onde a utilização de glicerina bruta reduz os teores de colesterol, não causando prejuízos a saúde animal.…”
Section: Resultados E Discussõesunclassified
“…Metal pesado é todo elemento com alto caráter tóxico, densidade maior que 6 g cm -3 e que apresenta relação direta com poluição (SANTOS;BATISTA, 2015). Podem ser divididos em essenciais e não essenciais.…”
Section: Metais Pesados Ou Elementos-traçounclassified
“…No estado de São Paulo, por influência do clima, existe meses que a produção de forragem é reduzida, assim como a qualidade nutricional(SANTOS et al, 2014). Esse período pode ocorrer no terço final da gestação da ovelha.…”
unclassified